Application of BIM in sustainability analysis - Golzarpoor, Hamed (2010)
Building Information Modeling (BIM) is the process of generating and managing building data during its life cycle. Typically it uses three-dimensional, real-time, dynamic building modeling software to increase productivity in building design and construction. The process produces the Building Information Model, which encompasses building geometry, spatial relationships, geographic information, quantities and properties of building components. On the other hand, Green Building Index (GBI) as the localized sustainability building rating system in Malaysia assesses the impact of building on environment based on energy efficiency, indoor environment quality, sustainable site & management, materials & resources, water efficiency and innovation. By integrating GBI assessment criteria with BIM technology, this research proposes a comparative case study analysis of Residential New Construction (RNC) and Non-Residential New Construction (NRNC) based on the Autodesk Ecotect Analysis software (a comprehensive, concept-to-detail sustainable design analysis tool that provides a wide range of simulation and analysis functionality through desktop and web-service platforms) and Autodesk Green Building Studio (A web-based energy analysis service which performs whole building analysis, optimizes energy efficiency, and works toward carbon neutrality earlier in the design process) to investigate the influence of construction material on energy consumption, lifecycle energy cost and carbon emission.